2021
DOI: 10.3390/ijms22052410
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Mesenchymal Stem Cells in Skin Regeneration and Rejuvenation

Abstract: Mesenchymal stem cells (MSCs) are multipotent stem cells derived from adult stem cells. Primary MSCs can be obtained from diverse sources, including bone marrow, adipose tissue, and umbilical cord blood. Recently, MSCs have been recognized as therapeutic agents for skin regeneration and rejuvenation. The skin can be damaged by wounds, caused by cutting or breaking of the tissue, and burns. Moreover, skin aging is a process that occurs naturally but can be worsened by environmental pollution, exposure to ultrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
96
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(98 citation statements)
references
References 150 publications
1
96
0
1
Order By: Relevance
“…For example, embryonic stem cells have the ability to differentiate into, but not limited to, blood or nerve cells ( Figure 2 a), while mesenchymal stem cells harvested from adult tissue have been found to differentiate into bone or cartilage cells, among others ( Figure 2 b) [ 25 ]. A recent study by Jo et al found that mesenchymal stem cells have beneficial effects on skin regeneration by promoting cell proliferation, decreasing skin inflammation, and increasing collagen and elastic fibers [ 26 ]. Another study in rats found that the direct injection of mesenchymal cells in radiation-wound areas in the skin of rats resulted in an injury area of about half the size when compared with the control group of rats at 14 days post injection [ 27 ].…”
Section: Classical Approaches To Tissue Engineeringmentioning
confidence: 99%
“…For example, embryonic stem cells have the ability to differentiate into, but not limited to, blood or nerve cells ( Figure 2 a), while mesenchymal stem cells harvested from adult tissue have been found to differentiate into bone or cartilage cells, among others ( Figure 2 b) [ 25 ]. A recent study by Jo et al found that mesenchymal stem cells have beneficial effects on skin regeneration by promoting cell proliferation, decreasing skin inflammation, and increasing collagen and elastic fibers [ 26 ]. Another study in rats found that the direct injection of mesenchymal cells in radiation-wound areas in the skin of rats resulted in an injury area of about half the size when compared with the control group of rats at 14 days post injection [ 27 ].…”
Section: Classical Approaches To Tissue Engineeringmentioning
confidence: 99%
“…Additionally, induced-pluripotent-stem-cell- (iPSC-) derived MSC have been reported to be suitable for cell therapy. However, their effectiveness in human patients remains to be established ( Jo et al, 2021 ; Mazini et al, 2021 ; Ullah et al, 2021 ). The proposal of proangiogenic paracrine secretion by stem and precursor cells cultured in microgravity has been provided ( Ratushnyy et al, 2018 ; Kong et al, 2021 ).…”
Section: Pharmacological Cellular and Physical Countermeasuresmentioning
confidence: 99%
“…Menstrual blood [ 5 ], tonsils [ 6 ], and induced pluripotent stem cells (iPSCs) [ 7 ] are also attracting attention as novel tissue sources for MSCs and are expected to be suitable as cell therapy products. The iPSC-derived MSCs have been applied to skin regeneration and skin rejuvenation [ 8 , 9 ], and menstrual blood-derived MSCs (MB-MSCs) have shown angiogenic potential similar to that of bone marrow-derived MSCs (BM-MSCs) [ 5 , 10 ]. Tonsil-derived stem cells have excellent proliferation and differentiation capabilities, and their clinical applications as therapeutic agents have been studied [ 6 , 11 , 12 ].…”
mentioning
confidence: 99%
“…To optimize the clinical applications, the approaches used to develop biological products based on the molecular properties of MSCs and their mechanisms of action are being studied. Among these approaches, the paracrine function of MSCs via the secretome, which involves conditioned media (CM), EVs, and exosomes, is considered to be representative [ 5 , 9 , 13 , 14 , 15 , 16 , 17 ]. The CM derived from BM-MSCs and MB-MSCs have been shown to be capable of stimulating tube-like formation of human umbilical vein endothelial cells [ 5 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation